(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The study involves the development of a simple, rapid, selective, and low-cost spectrophotometric method for the determination of ceftriaxone as pure and in its pharmaceutical preparations. The ceftriaxone (CF) was diazotized by sodium nitrite NaNO2 solution in the presence of hydrochloride acid HCl in the ice bath at range of 0 to 5 ºC to form diazonium salt, and then coupled with 4,5-diphenylimidazole reagent (4,5-DPI) in a basic solution of sodium hydroxide solution to form a purple color water–soluble azo dye as a result, that has a maximum absorption λmax at 550 nm opposite reagent blank, in the optimum conditions. The linearity of the process obeyed Beers law in the concentration range of 10 to 100 μg/mL at a correlation coefficient R2 of 0.9973. The molar absorptivity was 3772.08 L/mol.cm. The detection limit and quantification limits were 4.9425 and 16.475 μg/mL, respectively. Relative error and precision were determined to be 2.8% and 1.44%, respectively. The resulting stoichiometry of the AZO dye (drug: reagent) formed was found 1:1.